RESPONSE OF COLOURED RICE CULTIVARS TO ZINC NUTRITION - K , HIMASRI; K , ANNY MRUDHULA (The Journal of Research ANGRAU, 2026)
An experiment was conducted in the Farm of agricultural college, Bapatla, during kharif, 2023 to examine the response of zinc foliar fertilisation on the growth, yield attributes, yield and nutrient uptake of coloured rice (Oryza sativa L.). The experiment was laid by using split-plot design with three replications. The main plot contained four rice cultivars: M1- Navara, M2- BPT 2858, M3- BPT-2841 and M4- Kujipatalia. In the sub-plots, ZnSO4 foliar spraying was done at various stages: S1- No zinc, S2- Application of ZnSO4 @ 0.2% at tillering stage, S3- Application of ZnSO4 @ 0.2% at tillering and panicle initiation stages and S4- Application of ZnSO4 @ 0.2% at tillering, panicle initiation and booting stages. The results indicated that the Kujipatalia variety (M4 ) produced the maximum number of tillers, dry matter accumulation, productive tillers per square meter, panicle length, total grains per panicle, grain yield (4480 kg ha-1), straw yield, harvest index, and nutrient uptake. Foliar application of ZnSO„ at 0.2% during the tillering, panicle initiation, and booting stages (S4 ) was found to be significantly superior to other treatments, except for S3 . Conversely, the Navara variety (M1 ), when not received foliar zinc application, recorded the lowest values of all the parameters of coloured rice cultivars. However, it displays Kujipatalia variety shows highest yield and yield attributes relative to the other cultivars.